African military accounts and handbooks for British colonial Africa - Dorward, D. C. (Sources relating to Africa., 1978)
Information amassed by the War Office of Great Britain, on possible strategic importance regarding the military and economic potential of indigenous populations of Africa, their histories and local topography.